Feasibility Study of a Partner Bank Loan Scheme for Smallholder Palm Oil Replanting (PSR) - Maryadi; Sulastri, Merna Ayu; Antoni, Mirza (Jurnal AGRISEP, 2026)
Community oil palm plantations experience a decline in productivity when the oil palms are approximately twenty years old. Therefore, the government has launched a program in the form of community-led rejuvenation to restore production and maintain the long-term sustainability of farmers' income. This study attempts to examine and analyze the costs of rejuvenating small-scale oil palm commodities, including estimating the loan repayment period, monthly installment obligations, and opportunities when production and commodity price fluctuations impact farmers' ability to make repayments. The study was conducted at the Suka Makmur Palm Oil Producers Cooperative (KPKS) in Suka Makmur Village, Sungai Lilin District, Musi Banyuasin Regency, South Sumatra Province. Respondents were 397 cooperative member households. The financial feasibility study of oil palm commodity rejuvenation investments for farmers was conducted using the Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit-Cost Ratio (Net B/C) methods. The study results indicate that the proposed oil palm rejuvenation program implemented by KPKS Suka Makmur is financially feasible and generates positive economic returns. Farmers are projected to begin repaying the rejuvenation costs from the fifth to the 25th year. The estimated monthly installment is IDR 381,151 per hectare or approximately IDR 762,303 per plot. A sensitivity analysis indicates that financial viability is vulnerable to extreme conditions, including significant production declines, lower fresh fruit bunch prices, increased production costs, or increased loan interest rates. The study results emphasize the importance of risk management, production efficiency, and supporting policies to ensure the program's sustainability.